Volume 4: Heat Transfer, Parts a and B 2008
DOI: 10.1115/gt2008-51198
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Numerical Simulation of the Flow in a Direct Transfer Pre-Swirl System

Abstract: Results of fully unsteady numerical simulations of the flow in a direct transfer pre-swirl system are presented and compared with previously published experimental data from an aero-engine representative rig. The conditions considered include those where strong unsteady effects were observed experimentally. Two different rig builds are considered, with the main difference being in the design of the pre-swirl nozzles. The agreement between calculation and experiment is very good in terms of nozzle and receiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…It is considered that this will not affect the conclusions presented here. This unsteady model is similar to that of Ciampoli et al [27], with the addition of the inner cavity in some cases, as shown in the figure.…”
Section: Unsteady Modelsupporting
confidence: 68%
See 4 more Smart Citations
“…It is considered that this will not affect the conclusions presented here. This unsteady model is similar to that of Ciampoli et al [27], with the addition of the inner cavity in some cases, as shown in the figure.…”
Section: Unsteady Modelsupporting
confidence: 68%
“…The present unsteady simulations predicted very similar temperature drops to Ciampoli's [27] unsteady calculations, but predicted higher swirl velocity. Hence, the predicted temperature in Fig.…”
Section: Preswirl Deliverysupporting
confidence: 67%
See 3 more Smart Citations